Edukasi Aneka Olahan Hasil Pertanian dan Perikanan untuk Memenuhi Kebutuhan Nutrisi Anak di Galesong Kota Kabupaten Takalar: Education on Various Processed Agricultural and Fishery Products to Meet Children’s Nutritional Need in Galesong City, Takalar Regency - Liswahyuni, Andi; Ardiansyah, Muhammad; Tajuddin, Mustamin; Zukifli, Andi Tenriawaruwaty A. R.; Malik, Abdul; Tampubolon, Irianty; Kardi, Cening; Mahaji, Toga (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Takalar Regency, particularly in Galesong City, offers significant opportunities in agricultural and fisheries resources that have not been fully utilized to address nutritional problems in children. This community service is designed to enhance the knowledge and skills of mothers in Galesong City in processing local agricultural and fishery products into nutritious and appealing products for children, thereby meeting their nutritional needs. The approach used is participatory, consisting of socialization and determination of the need for healthys products for children; education on the importance of balanced nutrition and the use of local resources; demonstration and training in the manufacture of various processed foods, such as fish nuggets with vegetables, shredded fish with high protein content, cakes made from sweet potatoes or cassava enriched with fish or eggs, and other innovative preparations; training on how to package attractive and hygienic products; basic training on marketing to support home-based business potential. Mothers from Galesong City are expected to be involved and apply the knowledge they gain in their daily lives. The program was evaluated based on participants' understanding of nutrition and nutritious products, their improvement in food processing skills, and the increase in children's interest in healthy foods of local origin. This helps mothers create a diverse range of nutritious foods, increase children's intake, and improve their nutritional status. In addition, this program is expected to encourage innovation in local food processing, open up opportunities for MSMEs in processing based on local agricultural and fishery resources, and improve the welfare of local communities.